2010
DOI: 10.5551/jat.4135
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Polyunsaturated to Saturated Fatty Acid Ratio to Cardiovascular Risk Factors and Metabolic Syndrome in Japanese: the INTERLIPID Study

Abstract: Aim:There have been few studies on the relationships of the dietary polyunsaturated to saturated fatty acid ratio (P/S) to cardiovascular risk factors and metabolic syndrome. We hypothesized that there would be favorable relationships. Methods: Metabolic cardiovascular risk factors from dietary nutrient intake were investigated in 1,004 men and women aged 40 − 59 years from 4 population samples of Japanese. Multiple linear regression analysis was used to examine the relationship of the dietary P/S ratio to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
(41 reference statements)
0
13
0
1
Order By: Relevance
“…The n-6/n-3 ratios varied between 1.4 (in C1) and 4.1 (in C3) (Table 5). Recent studies have shown that a balanced intake of dietary PUFA and SFA (ranged between 1.0 and 1.5) can contribute to reduce cardiovascular diseases [23,24]. The glycerophospholipids from pulp/peel oils of subspecies sinensis , rhamnoides and mongolica presented greater amounts of the 18:2n-6 (25.7%, 24.2% and 32.1%, respectively) and 18:3n-3 (15.4%, 12.9% and 10%, respectively) fatty acids than those of corresponding PLs from the present study [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…The n-6/n-3 ratios varied between 1.4 (in C1) and 4.1 (in C3) (Table 5). Recent studies have shown that a balanced intake of dietary PUFA and SFA (ranged between 1.0 and 1.5) can contribute to reduce cardiovascular diseases [23,24]. The glycerophospholipids from pulp/peel oils of subspecies sinensis , rhamnoides and mongolica presented greater amounts of the 18:2n-6 (25.7%, 24.2% and 32.1%, respectively) and 18:3n-3 (15.4%, 12.9% and 10%, respectively) fatty acids than those of corresponding PLs from the present study [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Our study could not examine the association between individual fatty acid intakes and dyslipidemia patterns due to the lack of a complete nutrient database; data on the levels of various types of fatty acids in Korean foods were not available. However, previous studies conducted in a Japanese population reported favorable effects of polyunsaturated fatty acids on blood lipids [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, high intake of polyunsaturated fatty acids was inversely associated with TC and LDLC levels [21] but positively associated with HDLC levels [22]. However, only limited data are available on the associations between overall lipid profiles and dietary factors.…”
Section: Introductionmentioning
confidence: 92%
“…It is well documented that the recommended consumption of PUFA lowers TC: high density lipoprotein ratio, improves insulin sensitivity, normalizes blood pressure and reduces systemic inflammation [27]. Available data suggest that increasing the P/S ratio to 1.0 (approximately 1.0-1.5) would reduce the risk of atherosclerosis and MetS [28].…”
Section: Discussionmentioning
confidence: 99%